2017
DOI: 10.1080/13546805.2017.1399114
|View full text |Cite
|
Sign up to set email alerts
|

Self-reference in suicidal behaviour

Abstract: Overall, measures of the narrative self were not directly associated with suicidality. However, biased self-perception was related to painful and depressive feelings, which were in turn related to suicidal ideas. More research on self-related processing during the suicidal process is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Among a community sample of adolescents, endorsement of negative self-referential statements predicted suicide ideation at a 2-year follow-up assessment, above and beyond baseline depression symptom severity ( 33 ). In contrast, in a study directly comparing depressed adults with a lifetime suicide attempt history and depressed control subjects with no lifetime STB history, there were no significant differences related to endorsement and recall of negative self-referent information ( 34 ). Despite mixed support for behavioral self-referential processes characterizing STBs, alternative approaches may yield clearer insight.…”
Section: Negative Self-referential Processing and Suicide Riskmentioning
confidence: 79%
“…Among a community sample of adolescents, endorsement of negative self-referential statements predicted suicide ideation at a 2-year follow-up assessment, above and beyond baseline depression symptom severity ( 33 ). In contrast, in a study directly comparing depressed adults with a lifetime suicide attempt history and depressed control subjects with no lifetime STB history, there were no significant differences related to endorsement and recall of negative self-referent information ( 34 ). Despite mixed support for behavioral self-referential processes characterizing STBs, alternative approaches may yield clearer insight.…”
Section: Negative Self-referential Processing and Suicide Riskmentioning
confidence: 79%
“…We observed that suicide attempters had higher level of negative self-reference, which is consistent with the literature. Suicidal behaviors and negative self-reference seem to have a bidirectional link: self-contempt may be a risk factor for suicidality and suicidal behaviors lead to negative attitude toward oneself (Jollant et al, 2017;Rüsch et al, 2019;Solano et al, 2019). Moreover, recent findings based on the assessment of functional connectivity between neuronal networks, showed particular patterns of activation of the Default-Mode Network (DMN) supporting selfreferencing process, in suicide attempters vs. non-attempters suffering from MDD, and healthy controls.…”
Section: Association Between Suicidality and Negative Self-reference mentioning
confidence: 99%
“…The DMN plays an important role in "internal mentation"-the introspective and adaptive mental activities in which humans spontaneously and deliberately engage [48]. Several lines of evidences suggest a perturbed sense of self in people who attempt suicide [49,50]. Suicidal activity in mood disorder patients may be also a consequence of impaired self-referential thought processing [15].…”
Section: Discussionmentioning
confidence: 99%